The Private Houses of Kharkiv Citizens in 1860s and in the Begining of 20 Century : semiotic analyze - Нестеренко, Вікторія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
Article is about correlation between appearance of the private buildings of the Kharkiv citizens and their vision of their own houses. The development of the city in 1860th is compared with the one of the early XX century. The correlation between region of location of the building and social status of the owner is studied.